Effect of Medicaid accountable care on preventable emergency department and hospital admissions: rural-urban heterogeneity - Yoon, Jangho; Ghim, Seungbeen; Luck, Jeff (Frontiers in Health Services, 2025)
BackgroundAccountable care organizations provide a framework for collaboration among providers and payers to improve patients’ health and care experiences while reducing costs. However, there is limited research on the realization of these benefits for low-income individuals across varying degrees of rurality. This study examined the heterogeneous impact of Coordinated Care Organizations (CCOs), an accountable care model implemented in Oregon Medicaid, on preventable emergency department (ED) and hospital admissions by rurality of residence.MethodsUsing person-month panel data on 131,246 adults aged 18–64 continuously enrolled in Oregon Medicaid between 2011 and 2015, we employed a doubly-robust difference-in-differences approach to isolate the impacts of the CCO model on the number of ED visits and the probability of hospital admissions, separately for all-cause and preventable admissions.ResultsThe CCO model was associated with reductions of 25 all-cause ED visits and 22 preventable ED visits per 1,000 persons per month during the first three years. Significant decreases in all-cause and preventable ED visits were observed across different levels of rurality. However, the magnitude of these reductions decreased almost monotonically as rurality increased from urban to small/isolated rural areas. On average, the CCO model was associated with significant declines in preventable ED visits by 18, 9, and 5 visits per 1,000 persons per month among urban, large rural, and small/isolated rural residents, respectively. No statistically discernable relationship was found for hospital admissions.ConclusionsThe CCO model led to significant overall reductions in preventable ED visits. However, this beneficial effect may diminish with increased rurality.